FINTECH LENDING DEVELOPMENT, RURAL BANK PERFORMANCE, AND COLLABORATION POTENTIAL: RURAL BANKS PERSPECTIVE - Nofa Hermawati; Irwan Trinugroho (Universitas Sarjanawiyata Tamansiswa, 2024)
The rapid development of information technology has brought the presence of fintech to the financial industry, which in turn has had a disruptive effect on banks that still run the business in traditional way, especially the rural banks that have a similar market share and relatively smaller resources. This study aims to examine the impact of fintech lending development on the rural bank performance and the potential for collaboration between fintech companies and rural banks in the Greater Solo Region based on rural banks’ perspective. The research uses primary data obtained from questionnaire survey that are analyzed by using an in-depth descriptive statistics and multiple linear regression analysis. The study discovers that the development of fintech lending in the Greater Solo area is considerably not really significant according to the rural banks’ perceptions. Furthermore, this research finds that the development of fintech lending has a negative effect on rural bank performance and a positive effect on the potential for collaboration between fintech companies and rural banks. This research contributes to providing recommendations for fintech companies and rural banks in building partnerships and for regulators in overseeing such collaborations to increase financial inclusion in Indonesia as a whole.